MODEL KOMUNIKASI SOSIAL KEAGAMAAN PEMERINTAH DAN TOKOH AGAMA DALAM MELAKUKAN PEMBINAAN TERHADAP MANTAN ANGGOTA GAFATAR DI KABUPATEN TRENGGALEK - Abu Amar Bustomi; Ulfah, Elok Maria; Muchlis (Center of Education Journal (CEJou), 2023)
The research questions addressed in this work are: 1) How models of social communication carried out by the government in fostering the former member Gafatar in Trenggalek ?. 2) How religious communication model made by religious leaders in fostering the former member Gafatar in Trenggalek?. 3) Whether the factors that prompted the government and religious leaders in fostering the former member Gafatar in Trenggalek ?. 4) Whether the factors that hinder the government and religious leaders in fostering the former member Gafatar in Trenggalek ?. This study used a qualitative approach in the design exploratory and ethnographic studies in the frame. Data collection techniques used is semistructured interviews, observation of non participant and documentation. After the data is collected, then analyzed using the techniques of analysis model template. The model is commonly used in ethnographic research, including research on the dynamics of the lives of individuals and groups. The research found out that: 1) Model of social communication carried out by the government in fostering the former member Gafatar in Trenggalek done using the approach communication patterns in the form of discussions, both formal and nonformal. In Addition, also be done by involving a former member Gafatar in any existingmutual assistance activities in the local communities. 2) Model of religious communication is done by religious leaders in fostering the former member Gafatar in Trenggalek done by providing an understanding of the true aqidah Islamiyah. In addition, also be done by involving a former member Gafatar in any religious activities in their local community, such as yasinan and tahlilan. 3) Factors that encourage government and religious leaders in fostering the former member Gafatar in Trenggalek consists of: psychological factors, factors means, and social factors. 4) Factors that hinder the government and religious leaders in fostering the former member Gafatar in Trenggalek namely the existence of barriers in terms of mindset and psychological factors perceived by a former member Gafatar.